Chronic low-grade inflammation in patients with systemic sclerosis is associated with increased risk for arteriosclerotic cardiovascular disease - Heilmeier, Ursula; Feldmann, Daria; Leynes, Andrew; Seng, Magdalena; Jandova, Ilona; Keute, Marius; Kollert, Florian; Voll, Reinhard Edmund; Finzel, Stephanie (Frontiers in Medicine, 2024)
Please see final abstract version as submitted with the final revised and annotated manuscript.